2011
DOI: 10.1007/s10695-011-9485-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of starving and feeding on some haematological and physiological responses of the Nile catfish, Clarias gariepinus exposed to copper at extreme seasons

Abstract: The lethal concentration for 50% of fish for 96h (96h LC(50)) of copper (Cu(2+)) was estimated for the Nile catfish (Clarias gariepinus) in extreme seasons, winter and summer, 4.31 and 4.79 mg/l, respectively. The Nile catfish was exposed to 96h LC(50) of copper for 7 days in extreme winter and summer. The body indices, haematological parameters as well as some plasma and liver enzyme activities and metabolite level were significantly differed in fish exposed to copper over than those of the control fish. Most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 59 publications
(87 reference statements)
0
1
0
Order By: Relevance
“…In the current study, the decrease in ALP activity of Coexposed fish may result from disruption of the membrane transport system, while tissue damage may be correlated with the increase in activity (Abdel-Hameid, 2011). The present study showed a significant increase in blood G levels in Co-exposed fish after 30 days of exposure.…”
Section: Serum Enzymes and Parametersmentioning
confidence: 55%
“…In the current study, the decrease in ALP activity of Coexposed fish may result from disruption of the membrane transport system, while tissue damage may be correlated with the increase in activity (Abdel-Hameid, 2011). The present study showed a significant increase in blood G levels in Co-exposed fish after 30 days of exposure.…”
Section: Serum Enzymes and Parametersmentioning
confidence: 55%